Blending poly (3-hydroxybutyrate) with polyethylene glycol (PEG): Thermal behaviour and rheological study - Norfarisha, Achim; Hazlina, Husin; Zulkafli, Hassan (Faculty Mechanical Engineering, UMP, 2019)
Poly (3-hydroxybutyrate) (PHB) is a biodégradable polymer which its application in industrial was limited due to sensitive to high processing temperature and poor mechanical properties. The thermal and rheological behavior for blends of PHB extracted from dry weight of Jatropha and Poly (ethylene glycol) (PEG) were investigated. Blends of PHB/PEG (PHB 100, PHB 80, PHB 60 and PHB 50) have been prepared through solution blending method. The thermal using Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) and rheological behavior using Oscillating Disk Rheometer have been investigated. The results indicate all PHb/PEG blends showed decreased at lowest melting temperature crystallinity (Xc). The TGA result showed that PHB 80 less degraded and suggest better thermal stability compared to PHB 60 and PHB 50. Adding PEG to PHB also improved the rheological behavior of PHB. At higher frequency range, PHB 100 showed less dependency on frequency indicating the elastic structure it has compared to PHB 80, PHB 60 and PHB 50.